Perception of the dwellers of the Capoeirana, municipality of Nova Era (MG), about the socioeconomic and environmental impacts understanded by the exploitation of emerald (Research, Society and Development, 2018)
The mining is the manual form of the ground exploration that has the purpose of extracting minerals, having an important function for the economy of the country. On the other hand, this activity triggers direct negative impacts, deteriorating the environment. The objective of this study was to analyze the perception of the Capoeirana residents, municipality of Nova Era (MG), about the socioeconomic and environmental impacts triggered by emerald exploration in the region using a questionnaire applied to 180 residents in this locality. Considering the socioeconomic impacts, the improvement in the financial aspects, represented by the acquisition of consumer goods, stands out; and social, since they all live on paved streets, they have piped water and electricity. With regard to the environmental impacts, it is possible to emphasize the withdrawal of the native vegetation for the opening of cavas, which are abandoned after their exhaustion.